Analisis Gaya Bahasa dan Majas pada Lirik Lagu “Hujan” Karya Utopia - Christian Adhityapranata; Daffa Adlan (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
The song "Hujan" is one of the songs popularized by the band Utopia, a band from Indonesia. The band Utopia is known as a pop-rock music genre and Utopia was formed in the 2000s and the song "Hujan" is a song released in 2007 which has strong vocals and a melancholic melody that makes it one of the musical works that is interpreted as an expression of feelings of sadness and longing that are hard to forget. In addition to its touching melody, the strength of the lyrics of this song also lies in the use of language style and figures of speech that enrich the meaning and emotions that are intended to be conveyed. Then the rain of Utopia itself describes the mood and feelings buried in sadness and silence accompanied by the falling rain. Through the lyrics, the singer expresses deep feelings for someone who has left, while reminiscing about the beautiful memories that once existed and this song describes how rain becomes a friend of loneliness and sadness and becomes a reminder of the unforgettable past